Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
(2xy)³
Step-by-step explanation:
According to the Power Rule of Exponents:
[tex](ab})^{m} = a^{m}b^{m}[/tex]
We can apply the Power Rule of Exponents to the given exponential expression, 8x³y³, by taking the smallest factor that when cubed (or raised to an exponent of 3), will produce the same results as the original exponential expression.
8 is a perfect cube of 2: ⇒ 2 × 2 × 2 = 2³ = 8
The cube of x is x³: ⇒ x × x × x = x³
The cube of y is y³ ⇒ y × y × y = y³
Hence, we can take the least common factors, (2xy) and raise them to the third power:
(2xy)³ = 2³x³y³ = 8x³y³
Therefore, the correct answer is: (2xy)³
[tex]\\ \sf\longmapsto 8x^3y^3[/tex]
- 8=2^3
- x^3=(x)^3
- y^3=(y)^3
We know the rule of exponents
[tex]\boxed{\sf (ab)^m=a^mb^m}[/tex]
Now
[tex]\\ \sf\longmapsto 8x^3y^3[/tex]
[tex]\\ \sf\longmapsto 2^3x^3y^3[/tex]
[tex]\\ \sf\longmapsto (2xy)^3[/tex]
[tex]\\ \sf\longmapsto (2xy)(2xy)(2xy)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.